Association of Premature Menopause With Risk of Abdominal Aortic Aneurysm in the Women's Health Initiative. Issue 6 (4th December 2022) - Chou, Elizabeth L.; Pettinger, Mary; Haring, Bernhard; Allison, Matthew A.; Mell, Matthew W.; Hlatky, Mark A.; Wactawski-Wende, Jean; Wild, Robert A.; Shadyab, Aladdin H.; Wallace, Robert B.; Snetselaar, Linda G.; Madsen, Tracy E.; et al.
Abstract : Objective: To determine if premature menopause and early menarche are associated with increased risk of AAA, and to explore potential effect modification by smoking history. Summary of Background Data: Despite worse outcomes for women with AAA, no studies have prospectively examined sex-specific risk factors, such as premature menopause and early menarche, with risk of AAA in a large, ethnically diverse cohort of women. Methods: This was a post-hoc analysis of Women's Health Initiative participants who were beneficiaries of Medicare Parts A&B fee-for-service. AAA cases and interventions were identified from claims data. Follow-up period included Medicare coverage until death, end of follow-up or end of coverage inclusive of 2017. Results: Of 101, 119 participants included in the analysis, the mean age was 63 years and median follow-up was 11.3 years. Just under 10, 000 (9.4%) women experienced premature menopause and 22, 240 (22%) experienced early men-arche. Women with premature menopause were more likely to be overweight, Black, have >20 pack years of smoking, history of cardiovascular disease, hypertension, and early menarche. During 1, 091, 840 person-years of follow-up, 1125 women were diagnosed with AAA, 134 had premature menopause (11.9%), 93 underwent surgical intervention and 45 (48%) required intervention for ruptured AAA. Premature menopause was associated with increased risk of AAA [hazard ratio 1.37 (1.14, 1.66)], but the association was no longer significant after multivariable adjustment for demographics and cardiovascular disease risk factors. Amongst women with ≥20 pack year smoking history (n = 19, 286), 2148 (11.1%) had premature menopause, which was associated with greater risk of AAA in all models [hazard ratio 1.63 (1.24, 2.23)]. Early menarche was not associated with increased risk of AAA. Conclusions: This study finds that premature menopause may be an important risk factor for AAA in women with significant smoking history. There was no significant association between premature menopause and risk of AAA amongst women who have never smoked. These results suggest an opportunity to develop strategies for better screening, risk reduction and stratification, and outcome improvement in the comprehensive vascular care of women.